Monetary Policy and the Price Behavior in Emerging Stock Markets - Cornelius, Peter (IMF Working Papers; Working Paper ;, 1991)
This paper examines whether the six largest and most active emerging stock markets are informationally efficient with respect to changes in the money supply. To investigate if stock prices fully reflect the information contained in money supply changes, two different econometric techniques are employed. First, direct Granger-causality tests are used, which locus on the short-run relationship between stock prices and money. Second, the long-run behavior of the two variables is studied by means of co-integration tests. The results suggest that at least for two markets profitable trading rules can be developed to earn consistently higher-than-normal rates of return.